Identification of Type 2 von Willebrand Disease in Previously Diagnosed Type 1 Patients: a Reappraisal Using Phenotypes, Genotypes and Molecular Modelling - Nitu-Whalley, Ioana C.; Riddell, Anne; Lee, Christine A.; Pasi, K. John; Owens, Dale; Enayat, M. Said; Perkins, Stephen J.; Jenkins, P. Vincent (Thrombosis and Haemostasis, 2000)
In order to investigate the possibility that qualitative type 2 defects in von Willebrand factor (VWF) occurred in patients previously diagnosed with quantitative type 1 von Willebrand disease (VWD), the phenotypes and genotypes were reanalysed in 30 patients who exhibited discrepant VWF activity/VWF:Ag ratios of less than 0.7. The capacity of VWF to bind to glycoprotein Ib (GpIb) was reassessed using the ristocetin co-factor activity (VWF:RiCo) assay compared to an in-house and a commercial ELISA assay (based on a mAb directed against the GpIb binding site on VWF). This was supplemented by multimeric analysis and the amplification and sequencing of a 936 bp fragment of exon 28 of the VWF gene with the aim of identifying mutations in the A1 domain. On reappraisal, using the VWF:RiCo assay all patients demonstrated a disproportionately reduced VWF:RiCo/VWF:Ag ratio, indicative of a qualitative defect, while abnormal ratios were detected in only seven kindreds using the in-house ELISA assay and in only one kindred with the commercial ELISA assay. Eight single amino acid substitutions were found in nine kindreds, four of which were novel candidate VWF mutations and four previously described in association with type 2 VWD. In agreement with the phenotype, the novel VWF mutations were located in the VWF-A1 crystal structure at positions that corresponded to potential type 2M defects. This study underlines the difficulties of correct diagnosis of the subtype of VWD and emphasises the importance of using sensitive phenotypic assays, the relevance of the VWF:RiCo/ VWF:Ag ratio, multimeric analysis and molecular modelling analysis.
Keywords: von Willebrand disease; VWF:RiCo/VWF:Ag ratio; VWF plasma multimers; genotype; molecular modelling